Supply Chain Management Practices and Supply Chain Integration on Organizational Performance: The Mediation Role of Competitive Capabilities - Poppy Laksita Rini; Aswin Kumar; Aftoni Sutanto (Journal of Management and Business Insight, 2023)
Purpose- This study's goal is to ascertain how competitive capabilites through supply chain management and supply chain integration affect organizational performance. Design/Methodology/Approach- Structural Equation Modeling, assisted by the Smart PLS program, is the data processing technique utilized in this study to examine the impact of the indicators of each of the aforementioned variables on Batik Micro, Small and Medium Enterprises in the Special Region of Yogyakarta. By distributing questionnaires, the researchers were able to collect data from up to 65 respondents. Findings- The findings of this study demonstrate that supply chain management and supply chain integration have a favorable impact on organizational performance, and that competitive skills can mediate that effect. Research limitations/implications- The study's findings are anticipated to serve as a guide and source of knowledge for business players, particularly Batik Micro, Small, and Medium Enterprises in Special Region of Yogyakarta, who are expected to understand that in order to enhance the performance of their enterprise, attention must be paid to elements that may have an impact.  This study demonstrates that competitive competencies, supply chain integration, and supply chain management techniques are all elements that can impact a company's performance. Originality/value- There are still very few studies on supply chains and organizational performance in micro, small, and medium-sized businesses, particularly Batik. In this study, characteristics that are thought to have an impact on the number of Batik Micro, Small, and Medium Enterprises in a Special Region of Yogyakarta are revealed.